Follower Attributes: Perceptions of Leadership and Followership Experts in the United States - Prilipko, Evgenia V. (Journal of Leadership, Accountability and Ethics, 2019)
This study identifies the most important characteristics of followers as perceived by followership and leadership experts in the United States. The grounded theory constructed as a result of the study reveals that (a) scarcity of followership courses in academic curricula can be explained by the negative stereotype of the term follower prevalent in the Western society, (b) follower skills can be taught, (c) followership should be taught every time leadership is taught at academic levels ranging from high school to post graduate, and (d) 17 follower attributes are suggested for the purpose of teaching individuals.